Evaluation of Antibacterial Efficacy and Phytochemical Screening of Root Extracts of Pimpinella heyneana (DC) Benth - Dr. Lingaraju D P; Sowmya H K (International Journal of Pharma and Bio Sciences, 2020)
The phytochemical research based on ethnobotanical information is generally considered as an effective approach in the discovery of novel antimicrobial agents from higher plants.Medicinal plants contain large varieties of chemical substances which possess important therapeutic properties that can be utilized in the treatment of infectious diseases. Now a day’s maximum number of plants are being screened for their possible pharmacological value. Pimpinella heyneana is a traditional medicinal plant. Its seeds and roots are used in the treatment of gum swellings, diarrhoea, and also as an antiseptic agent by the tribal communities of Kerala and Karnataka. The present study aimed to screen phytochemical constituents and to evaluate the antibacterial activity of root extracts of Pimpinellaheyneana. The root extracts were isolated using different organic solvents petroleum ether, chloroform, ethyl acetate, and methanol by soxhlet apparatus. Preliminary phytochemical screening revealed the presence of steroids, triterpenoids, flavonoids, and glycosides. Antibacterial activity was conducted against five human pathogenic bacterial strains, i.e. E.coli MTCC 7410, Staphylococcus aureus MTCC 7443, Klebsiella pneumoniae MTCC 7028, Enterococcus faecalis MTCC 9845 and Enterobacter aerogenes MTCC 7324 by disc diffusion method on nutrient agar media. The findings showed potential antibacterial properties of the extracts against the bacterial strains tested. Among the four solvents tested, the methanol extract of root showed maximum zone of inhibition. Methanol extract exhibits a maximum zone of inhibition against Escherichia coli, Enterococcus faecalis,and Enterobacter aerogenes. The methanolic extracts from the plant can be used to control infections caused by E. aerogenes, E. coli, and S.aureus. The results obtained in this study justify the use of P. heyneana by traditional medical practitioners.